Pengaruh PDRB, TPAK, IPM terhadap Tingkat Kemiskinan melalui Zakat sebagai Variabel Moderasi di Provinsi Jambi Tahun 2018-2022 - Nengsih, Titin Agustin; Andriani, Beid Fitrianova; Sugiharto, Joko (ARZUSIN, 2024)
This study aims to look at the effect of GNP, TAX, IPM on poverty levels through zakat as a moderating variable in Jambi province in 2018-2022. The type of research used is quantitative research. The location of this research is Jambi Province with a total of 11 districts and cities. The data sources in this study were obtained from the website of the Central Statistics Agency (BPS) and the National Amil and Zakat Agency (BAZNAS) of Jambi Province. Based on the results of data analysis, the following tasks were concluded. First, Simultaneously the variables of Gross Regional Domestic Product (GRDP), Labour Force Participation Rate (TPAK), Human Development Index (HDI) have a significant effect on the Poverty Level. Second, partially zakat cannot moderate Gross Regional Domestic Product (GRDP), Labour Force Participation Rate (TPAK), Human Development Index (HDI) on Poverty Level. Third, simultaneously zakat can moderate Gross Regional Domestic Product (GRDP), Labour Force Participation Rate (TPAK), Human Development Index (HDI), to the level of Poverty Level.